PENGEMBANGAN PEMBINAAN PROFESI DAN KODE ETIK PEREKAYASA - EDY SYAMSUDDIN (JURNAL EKONOMI, SOSIAL & HUMANIORA, 2021)
The success of developing a functional engineer position is carried out by coaching and resolving the problem of increasing the professionalization of the engineer who is a part that is really needed through the basic values approach of the code of ethics. The purpose of professional development and engineering code of ethics is to develop the engineering profession according to their competence and to follow the pattern of rules of the game in professional development by referring to the engineer code of ethics. Basic values, practical rules and professional bonds are guidelines to instill a spirit of professionalism and practice ethics for Civil Servants, so that Engineers are strong, compact and united, have sensitivity, are responsive and have high solidarity, are disciplined. and aware of their responsibilities as an element of the state apparatus and public servants. The function of professional development and professional code of ethics provide guidelines for every member of the profession regarding the principles of professionalism outlined; Professional code of ethics is a means of social control for the community over the profession concerned; and the existence of a professional code of ethics to prevent interference from parties outside professional organizations regarding ethical relationships in professional membership. To design professional coaching and develop a professional code of ethics for engineering functional positions, several methodological approaches were carried out, namely with several references from the professional development process and code of ethics from engineering associations in America, such as from NSPE, ASME, ASCE, and as a basis for reference to the code of ethics. Civil servants in accordance with PP.No. 24, year 2004. The approach pattern is the concept of basic values which consists of seven principles, then the main issue in the engineering code of ethics, namely, respecting the rights of individuals and companies, being responsible, having competency values and having competency values both from their work and abilities and expertise.